THE INFLUENCE OF VILLAGE FINANCIAL SYSTEM, APPARATUS COMPETENCE, AND KNOWLEDGE ON FINANCIAL ACCOUNTABILITY VILLAGES IN AMPANA TETE - Lanonci, Nurwasilah; Masdar, Rahma; Mustamin, Mustamin; Masruddin, Masruddin; Din, Muhammad (Jurnal Manajemen Terapan dan Keuangan, 2025)
This study aims to analyze the influence of the use of the Village Financial System (Siskeudes), village apparatus competency, and knowledge on accountability in village financial management in Ampana Tete District. This study used a quantitative approach, with a population of all village apparatus involved in financial management. The sampling technique used was a census, involving 80 respondents from 20 villages. Data were collected through structured questionnaires, interviews, observations, and documentation. Data analysis was conducted using multiple linear regression after validity and reliability tests, as well as classical assumption tests. The results show that the use of Siskeudes has a positive effect on accountability, as evidenced by the accuracy of recording and transparency of reporting. The competency of village apparatus was proven significant through their understanding of regulations and technological literacy. Furthermore, the apparatus' computer knowledge supports the effectiv This study aims to analyze the influence of the use of the Village Financial System (Siskeudes), village apparatus competency, and knowledge on accountability in village financial management in Ampana Tete District. This study used a quantitative approach, with a population of all village apparatus involved in financial management. The sampling technique used was a census, involving 80 respondents from 20 villages. Data were collected through structured questionnaires, interviews, observations, and documentation. Data analysis was conducted using multiple linear regression after validity and reliability tests, as well as classical assumption tests. The results show that the use of Siskeudes has a positive effect on accountability, as evidenced by the accuracy of recording and transparency of reporting. The competency of village apparatus was proven significant through their understanding of regulations and technological literacy. Furthermore, the apparatus' computer knowledge supports the effective use of Siskeudes and enhances accountability. This study emphasizes the importance of improving apparatus competency and digital literacy in supporting transparent and accountable village financial governance. This research is limited to one sub-district and is based solely on the perspective of internal village apparatus. e use of Siskeudes and enhances accountability. This study emphasizes the importance of improving apparatus competency and digital literacy in supporting transparent and accountable village financial governance. This research is limited to one sub-district and is based solely on the perspective of internal village apparatus.